2019
DOI: 10.1039/c9tc00972h
|View full text |Cite
|
Sign up to set email alerts
|

A laminar MAPbBr3/MAPbBr3−xIx graded heterojunction single crystal for enhancing charge extraction and optoelectronic performance

Abstract: A laminar MAPbBr3/MAPbBr3−xIx graded heterojunction single crystal forms a graded valence band structure, resulting in enhanced hole extraction as well as superior photodetection performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The series of distinct characteristic peaks and small full width at half-maximum of the MAPbCl 3 PSC on epitaxial MAPbBr 2.5 Cl 0.5 indicate the high-quality crystallization. In addition, its diffraction peak positions nearly overlap with MAPbBr 2.5 Cl 0.5 PSC and MAPbCl 3 PSC, which corresponds to the reported graded heterojunction (Li et al, 2019b ). The existence of main and secondary peaks in the XRD spectra of MAPbCl 3 PSC on epitaxial MAPbBr 2.5 Cl 0.5 is attributed to the diffraction of both thin epitaxial MAPbBr 2.5 Cl 0.5 layer and MAPbCl 3 layer.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The series of distinct characteristic peaks and small full width at half-maximum of the MAPbCl 3 PSC on epitaxial MAPbBr 2.5 Cl 0.5 indicate the high-quality crystallization. In addition, its diffraction peak positions nearly overlap with MAPbBr 2.5 Cl 0.5 PSC and MAPbCl 3 PSC, which corresponds to the reported graded heterojunction (Li et al, 2019b ). The existence of main and secondary peaks in the XRD spectra of MAPbCl 3 PSC on epitaxial MAPbBr 2.5 Cl 0.5 is attributed to the diffraction of both thin epitaxial MAPbBr 2.5 Cl 0.5 layer and MAPbCl 3 layer.…”
Section: Resultssupporting
confidence: 55%
“…Therefore, it is feasible to fabricate lattice-matched heterojunctions with the energy band gradient between MAPbBr 2.5 Cl 0.5 PSC and MAPbCl 3 PSC by epitaxy growth. This would significantly decrease the leaking current and accelerate carrier transport, leading to a high-performance PSC photodetector (Li et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Li et al showed conversion of MAPbBr 3 to MAPbBr 3– x I x using a gas–solid exchange reaction. 59 Another approach to this method is the seeded space-limited crystallization and printing approach. Gu et al prepared CsPbBr 3 , MAPbCl 3 , MAPbI 3 , (BA) 2 PbBr 4 , and (BA) 2 (MA) 3 Pb 4 Br 13 SCs using the general printing approach, as shown in Figure 5 d. 60 Yue et al confined the seed crystal of MAPbI 3 between two glass substrates to induce crystallization and produced SCs with thicknesses ∼50 μm and fabricated a solar cell with the architecture of ITO/PEDOT:PSS/MAPbI 3 /PCBM/Ag.…”
Section: Single-crystal Growth Methodsmentioning
confidence: 99%
“…After the perovskite film was prepared by the spaceconfined method, it could be converted into halide gradient perovskite film to further improve the performance of photoelectric devices. A facile conversion method was reported by Li et al Based on their previous work of growing perovskite by the space-confined method [35], they prepared halide gradient perovskite films by a space-limited inverse temperature crystallization growth method and a subsequent gaseous halide exchange process [75]. The gas-solid exchange process is illustrated in Fig.…”
Section: Components Regulatingmentioning
confidence: 99%